Our achievements at Cendekia Bitara Awards 2011 - Hafizoah, Kassim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
2 May 2012. Congratulations! Congratulations to both award receivers, Dr. Nik Aloesnita Nik Alwi and Nor Ashikin Abdul Aziz, who were recognized for their achievements during the Cendekia Bitara Awards 2011 ceremony. Cendekia Bitara Award was inspired by the university to award and acknowledge UMP associates for their achievements in research and development (R&D), publication and teaching. To recognize the efforts and achievements of UMP associates for 2011, the Cendekia Bitara Award 2011 was held on 28 April 2012 at Hyatt Regency Hotel, Kuantan.